E-Conomics Strategies for the Digital Marketplace - Zerdick, Axel; Schrape, Klaus; Artope, Alexander; Goldhammer, Klaus (European Communication Council Report, 2000)
The Internet transformed the landscape of world economy. E-conomics provides readers a roadmap to this new landscape, a systematic reference guide to economics in the information age and serves as the first textbook available. Scientists in communication economics from the U.S. and Europe have collaborated to provide an in-depth analysis of the Internet revolution, showing how the rules of the game have changed in an economy trading information instead of industrial goods. E-conomics focuses on the European telecommunications industry and features strategies for a successful Network Economy, as well as an emphasis on network infrastructure and the importance of compatible technological standards. Some perspectives given in 1998, when the original version appeared, became reality since. This book is essential reading for economists and business strategists requiring an understanding of the dynamics of electronic commerce. The underlying data was kept up to date